The Effect of Non-Physical Work Environment and Work Productivity on Employee Performance at Mr. DIY Sukabumi City - Faizal Mulia Z; R. Deni Muhammad Danial; Anggia Puspa Ardiani (Inovbiz: Jurnal Inovasi Bisnis, 2023)
The purpose of this study was to determine the description of non-physical work environment, work productivity, and employee performance at Mr. DIY Sukabumi City, to determine the effect of non-physical work environment on employee performance at Mr. DIY Sukabumi City, and to determine the effect of work productivity on employee performance at Mr. DIY Sukabumi City. The phenomenon that occurs in the performance of employees of Mr. DIY Sukabumi City is lacking in terms of employee work quality, namely the lack of employee ability in work. This problem is caused by one of the dimensions in the nonphysical work environment, namely leader attention and support. In this case, the leader does not give appreciation to the work of employees. Another cause is the ability which is one of the factors in work productivity, namely the lack of employee skills so that it cannot improve work efficiency and effectiveness. In this case, employees do not have sufficient knowledge about the products sold at Mr. DIY so that it affects employees in making sales. The methods used in this research are descriptive research methods and associative research methods with a quantitative approach. The sampling technique used by researchers is a saturated sample technique, which is a total of 30 respondents. The data analysis technique used is the classical assumption test, multiple linear regression analysis which includes the coefficient of determination, multiple correlation coefficients and partial tests (t test). The results showed that partially the non-physical work environment affects employee performance. Work productivity affects employee performance. The contribution of the influence of non-physical work environment variables and work productivity on employee performance is 76.3%. While the remaining 23.7% is influenced by other variables outside this regression equation or variables not examined.